Peran Motivasi Kerja Sebagai Intervening Dalam Meningkatkan Performa Pegawai - Herman Sjahruddin; Tenri Rawe; Syamsul Ridjal; Ampauleng Ampauleng (Universitas Negeri Padang, 2022)
High employee performance is the hope of the organization, and for that more attention is needed from the management through the provision of remuneration, discipline creation, and increased motivation that is carried out. We developed and tested a model in which dicipline and remuneration affects performance indirectly, through the mediating effects of work motivation Explanatory research was conducted on 83 employees at the Regional Secretariat of South Sulawesi Province using PLS 3.0. This research provides evidence that the provision of remuneration and increased discipline in work is proven to have a real effect in increasing work motivation. Remuneration and work motivation make a significant contribution to improving employee performance to a higher level, except for work discipline. The role of motivation is divided into two (partial and complete mediation) in investigating the effect of remuneration and work discipline on performance